Os ciclos do fracasso escolar: concepções e proposições. - FARIA, Gina Glaydes Guimarães de (2008)
This theoretical study was developed according to the principles of the research field on cultural and educational processes. It aimed at reviewing the concepts of school failure present on the academic journal Cadernos de Pesquisa, published by Fundação Carlos Chagas, since its first issue, released in 1971, up to 2006. From the Marxian perspective, this work considers school failure a social product inherent to a society based on antagonistic classes. Through an analysis of themes, and theoretical and methodological references, it focused on how school failure was treated, based on the assumption that the concepts exhibited in this journal throughout this period expressed both comprehension of this subject and intervention processes in it. Despite the fact that in discussing issues regarding to education, the main concern has been mostly the fundamental education, the school level officially assured as compulsory and accessible to every citizen in Brazil. One hundred an ninety six articles which dealt directly or indirectly with school failure were selected from Cadernos de Pesquisa and analyzed according to a systematic listing of the documents, following the themes as well as theoretical and methodological principles predominant in each article. The changes in the concepts of the expression school failure were described, identifying the main aspects considered as modalities of culture emphasis: the emphasis on cultural marginalization, in its critical and propositional approaches; and also the emphasis on cultural diversity. The results revealed two main trends in the analyzed data: the prominence, present in most of them, of the relation between school failure and cultural differences, in opposition to the studies which focus on the relation between school failure and social disparity developed during the nineteen eighties, the redemocratization period of Brazilian society. The other trend is related to school management, considered as able to promote some adjustments to the school dynamics, sometimes based on the culture of school success, focusing on the students needs and cultural peculiarities. In a context of educational reforms which tend to cover social disparity for the sake of cultural differences, more subtle forms of justification for the school failure are possibly being generated